The decoration of the book by Lewis Carroll's “Alice in Wonderland” - Kasianova, Daria (ARTS AND MUSIC IN CULTURAL DISCOURSE. Proceedings of the International Scientific and Practical Conference, 2013)
The article discusses the features and basic requirements for the design of children's books. For example, was selected to the book by Lewis Carroll's "Alice in Wonderland." The purpose of this work: an analysis of the features of decoration of children's books by the example of author's illustrations to the tale of Lewis Carroll's "Alice in Wonderland" in connection with the upcoming celebration of the 150 year anniversary of the publication of the book in 1865. To achieve this goal has been studied history of fairy tales. Attention is paid to the choice of a suitable translation into Russian. Because the book is based entirely on English puns and witticisms, folklore, linguistic and philological subtleties, it is hard to understand Russian readers, and even more so for children. The analysis of the existing analogue illustrations and prototypes of the main characters of fairy tales. Detailed history of the characters. Studied costumes of the characters of the 19th century, faithfully reproduce the historical era. Together illustrations adapted to the modern reader. The examples of stylized characters. Defined the main age group of readers for whom the book is intended. In this regard, consider age features and requirements for registration. Formed the basic concept of decoration. It is the desire to approach most closely to the original text, and not to deviate from the real prototype in the direction of the stereotypical characters, falsely taken as a model to follow. At the same time reflects the problem of conformity visuals and content of the book. As the techniques of performing multi-layered watercolor technique chosen.